Synthesis and characterization of monoclinic gallium oxide nanomaterials for high-concentration ethanol vapor detection - Dela Torre, H. M. B. (Animo Repository, 2020)
This study was conducted to synthesize Gallium Oxide nanomaterials from its bulk form using a low-cost and repeatable method and investigate on its potential as sensing element for Ethanol (EtOH). Horizontal Vapor Phase Growth (HVPG) Technique was utilized to synthesize monoclinic Gallium Oxide (β-Ga2O3) nanowires. Images obtained from the Scanning Electron Microscope showed high density nanowires specifically in the area of highest temperature gradient. SEM also showed that the grown structures using HVPG Technique were at the nanoscale with diameters ranging from 51.60 to 908.38 nm. Higher surface-to-volume ratio was also noted in the area of highest temperature gradient which was subjected to an applied magnetics field. The Gallium to Oxygen ratio was verified via EDX to be approximately 2:3 which agrees with the atomic ratio of Ga2O3. The monoclinic structure of the grown nanomaterials was investigated using Raman Spectroscopy. Raman peaks of the samples were at 199 and 486 cm-1 which was accounted to the presence of two Raman-active modes of the b-polymorph of Ga2O3. The Raman spectrum of the grown nanowires confirmed that the material is monoclinic in structure and belongs to C2/m space group. The I-V Curve of the grown nanowires were also determined using two-point probe which illustrates a non-linear curve similar to that of a semiconductor material. Furthermore, additional fundamental properties such as resistivity and specific conductance of the materials were also determined via van der Pauw Technique. Results showed that the material has high specific conductance and low resistivity. The synthesized nanomaterial was responsive to Ethanol vapor. Exposure to the said compound increased its resistance. Graphs showed that there is a significant increase in the resistance after exposure to ethanol vapor. © 2020 IOP Publishing Ltd. All rights reserved.